Foreword 3(1) - Wach, Krzysztof; Knežević, Blaženka; Šimurina, Nika (International Entrepreneurship Review, 2017)
Regional idiosyncrasies of international business are recognized in both Central and Eastern Europe (CEE) and South-East Europe (SEE) countries. There is a theoretical and empirical gap in the literature, however, which is bridged by this thematic volume. It is important that the possibilities, which are created for businesses in the region of CEE and SEE, became fully utilized.This volume presents current research findings from different parts of Europe making a valuable polyphonic contribution to the puzzle of both regional business and international business nexus. It contains 13 papers grouped in two parts. The first one is dedicated to general issues such as business environment and entrepreneurial challenges, while the second part discusses specific industries and trends.This volume attempts to integrate general theory and empirics of specific industries and trends. The theory of business environment and entrepreneurial challenges focuses on economic determinates of entrepreneurial orientation in international business, while analysis of specific industries and trends deals with the dynamic evolution of comparative advantage and the consequences of international trade. In the light of dual focus of this study, we believe that it will be of interest both to business analysts and to international economists concerned with the evolution of trading patterns. Individual authors and the editors hope that readers will appreciate the work assembled here and that it will encourage further interests in these issues within the scope of CEE and SEE.